2014
DOI: 10.1002/ajp.22275
|View full text |Cite
|
Sign up to set email alerts
|

Personality and subjective well‐being in captive male western lowland gorillas living in bachelor groups

Abstract: The purpose of this study was to determine the personality structure of eight male gorillas (five silverbacks and three blackbacks) housed at the Sedgwick County Zoo in Wichita, Kansas and to determine if personality predicts behavior and subjective well-being in male gorillas living in bachelor groups. We used the Hominoid Personality Questionnaire which contains 54 descriptive adjectives with representative items from the human five-factor model. Rates of 12 behaviors that are broadly defined as agonistic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 46 publications
(127 reference statements)
4
38
0
Order By: Relevance
“…These factors showed interrater reliabilities and test-retest reliabilities comparable to those of human personality factors (e.g., Costa & McCrae, 1992) and personality traits and dimensions in other species (Bell, Hankison, & Laskowski, 2009;Gosling, 2001). The bonobo Assertiveness factor was similar to chimpanzee dominance (King & Figueredo, 1997;Weiss et al, 2007Weiss et al, , 2009 and to components and factors identified in other primate species (Eckardt et al, 2015;Konečná et al, 2008;Konečná et al, 2012;Morton et al, 2013;Schaefer & Steklis, 2014;Weiss et al, 2006Weiss et al, , 2011. In contrast, the evidence for chimpanzee analogues of extraversion and attentiveness was weak.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…These factors showed interrater reliabilities and test-retest reliabilities comparable to those of human personality factors (e.g., Costa & McCrae, 1992) and personality traits and dimensions in other species (Bell, Hankison, & Laskowski, 2009;Gosling, 2001). The bonobo Assertiveness factor was similar to chimpanzee dominance (King & Figueredo, 1997;Weiss et al, 2007Weiss et al, , 2009 and to components and factors identified in other primate species (Eckardt et al, 2015;Konečná et al, 2008;Konečná et al, 2012;Morton et al, 2013;Schaefer & Steklis, 2014;Weiss et al, 2006Weiss et al, , 2011. In contrast, the evidence for chimpanzee analogues of extraversion and attentiveness was weak.…”
Section: Discussionmentioning
confidence: 64%
“…Extraversion in bonobos differed from dimensions labeled extraversion, sociability, or friendliness in other species (Eckardt et al, 2015;King & Figueredo, 1997;Konečná et al, 2008;Morton et al, 2013;Schaefer & Steklis, 2014;Weiss et al, 2006Weiss et al, , 2007Weiss et al, , 2009Weiss et al, , 2011. The items "solitary," "depressed," "autistic," and "individualistic" all had negative loadings on this factor.…”
Section: Personality Structurementioning
confidence: 86%
See 2 more Smart Citations
“…Vazire et al, 2007); therefore, links between the two have been found and tend to be evident. For example, gorilla Dominance is related to received and given displacement (negative and positive, respectively) (Kuhar et al, 2006;Schaefer & Steklis, 2014); and Extraversion/Agreeableness is related to affiliative, grooming, playing, approach and touching behaviours (Schaefer & Steklis, 2014). Similarly, Chimpanzee Extraversion is related to affiliative behaviour (Pederson et al, 2005;Massen & Koski, 2014).…”
Section: Behaviour Management and Conservationmentioning
confidence: 99%